Late Na+ Current Is [Ca2+]i-Dependent in Canine Ventricular Myocytes - Dénes Kiss; Balázs Horváth; Tamás Hézső; Csaba Dienes; Zsigmond Kovács; Leila Topal; Norbert Szentandrássy; János Almássy; János Prorok; László Virág; Tamás Bányász; András Varró; et al. (MDPI AG, 2021)
Enhancement of the late sodium current (INaL) increases arrhythmia propensity in the heart, whereas suppression of the current is antiarrhythmic. In the present study, we investigated INaL in canine ventricular cardiomyocytes under action potential voltage-clamp conditions using the selective Na+ channel inhibitors GS967 and tetrodotoxin. Both 1 µM GS967 and 10 µM tetrodotoxin dissected largely similar inward currents. The amplitude and integral of the GS967-sensitive current was significantly smaller after the reduction of intracellular Ca2+ concentration ([Ca2+]i) either by superfusion of the cells with 1 µM nisoldipine or by intracellular application of 10 mM BAPTA. Inhibiting calcium/calmodulin-dependent protein kinase II (CaMKII) by KN-93 or the autocamtide-2-related inhibitor peptide similarly reduced the amplitude and integral of INaL. Action potential duration was shortened in a reverse rate-dependent manner and the plateau potential was depressed by GS967. This GS967-induced depression of plateau was reduced by pretreatment of the cells with BAPTA-AM. We conclude that (1) INaL depends on the magnitude of [Ca2+]i in canine ventricular cells, (2) this [Ca2+]i-dependence of INaL is mediated by the Ca2+-dependent activation of CaMKII, and (3) INaL is augmented by the baseline CaMKII activity.